The Opportunity of SMEs Development by Triple Helix ABG Method in Supporting Creative Economy in Pangkalpinang City - Mr Hamsani; Mr Khairiyansyah (Integrated Journal of Business and Economics)
Creative industries based on local wisdom are born from the creativity of the community who see the potential and unique characteristics in its region. Pangkalpinang City is the capital of the province of Bangka Belitung Islands always strives to improve economic development in improving the level of welfare of its people, one of them through the creation of SMEs. This study aims to identify and analyze how SMEs development opportunities by Tripple Helix ABG method in supporting creative economy in Pangkalpinang City. Kind of this research is descriptive qualitative approach by data collecting. This study is one of Small Research and Development (R & D) category. Respondents of this research are the beginner perpetrator of SMEs Creative Industry in Pangkalpinang City. The SMEs’ men are 61 persons. In this research, creative economy field covers 9 (nine) sectors: Advertising, Publishing and Printing, Fashion, Design, Research and Development, Information Technology, Architecture, Craft, and Interactive Games. The results of this study indicate the efforts and roles of each aspect of Triple Helix have not been so maximal, so further development opportunities can still be done.